Optical burst-mode coherent receiver with a fast tunable LO for receiving multi-wavelength burst signals - Mo Li; Ning Deng; Hauske, F. N.; Qingsong Xue; Xiaozhong Shi; Zhiyong Feng; Shiyi Cao; Qianjin Xiong (2011 Optical Fiber Communication Conference and Exposition and the National Fiber Optic Engineers Conference, 2012)
We propose a coherent burst-mode receiver structure for receiving multi-wavelength short PDM-QPSK optical bursts. Data-aided algorithms are employed for fast-tunable LO transients compensation and channel estimation to facilitate rapid data recovery.